General Introduction - Lackner, Michael (Handbook of Divination and Prognostication in China - Part One: Introduction to the Field, 2022)
The following introduction to the Handbook of Divination and Prognostication in China adopts the form of an itinerary around the coast of an island whose center seems to escape any ultimate characterization, because only outside perspectives are at our command. It is a periplus, the circumnavigating of the island of divination and prognostication in China and the different points of observation may shed some light on its evolution, its perception, its classifications, the presence of these phenomena in everyday life and their varying affinity to religion. Precisely because divination and prognostication were (and still are) pervasive, omnipresent and resilient in the culture of Chinese-speaking countries, a smallest common denominator for these practices is difficult to define. If one could leave aside the genealogical connotation of “family” in Wittgenstein’s theorem of “family resemblance” and could opt for the concept of a chain that connects certain (but not arbitrary) links, also inherent in Wittgenstein’s deliberations, the suggested periplus might lead us along those links of our itinerary’s voyage that help us gain insight into the multifaceted nature of our topic. And this way of a circumnavigation may be more helpful than any conventional form of introduction. After having read the first draft of this introduction, a friend of mine suggested a persistent fog that is preventing determining the location of that center. At times, patches of fog may be briefly lifting while we are circumnavigating it, but it remains evasive. With the present first volume of the Handbook, we are – to use yet another image from European Antiquity – entering a cave equipped with a torch, hitting upon an even more intricate complex of caves and trying to draw a map. The second volume will present the drawings on the wall.<br